Examining the factors influencing the consumer retention in Maybank's electronic banking services - Chang, Chia Qi; Chee, Yong Er; Ch’ng, Dylan Seng Huan; Goh, Yong Dian (2023)
The COVID-19 pandemic outbreak has significantly impacted the banking institution, especially accelerated the development and usage of electronic banking system. Due to the convenience of electronic banking, users of electronic banking have increased significantly, but there are also customer groups who refuse to adapt to the electronic banking system. Hence, this research is to examine the relationship between the six independent variables which included reliability, privacy and security, web design, customer services and support, responsiveness, service quality, and the dependent variable, customer’s retention in e-banking services in Malaysia. 300 online questionnaires were distributed to our targeted respondents which are Maybank2u users who reside in Malaysia. In this study, the data were analyzed using several analysis technics including descriptive analysis, reliability test, and collinearity statistics. The result shows that the reliability, privacy and security, web design, customer services and support, and service quality have significant impact on customer retention in e-banking services, whereas the responsiveness has insignificant impact on customer retention in e-banking services. Lastly, the limitations of this study and its recommendation has been discussed.